1963
DOI: 10.1016/0028-3908(63)90017-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chlorpromazine on some motor reflexes

Abstract: The effects of chlorpromazine (CPZ) on the patellar reflex and segmentally evoked spinal cord potentials were determined in various cat preparations. CPZ in doses of I-8 mg/kg given intravenously (as an accumulative dose) produced a signiticant depression of the patellar reflex and segmentally evoked potentials in animals with an intact central nervous system. Hypotension, potentiation of anesthesia, depression of nerve conduction in afferent and efferent nerves, an effect at the neuromuscular junction, or an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1964
1964
1980
1980

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…The antagonism of the decerebrate rigidity by the compound is in agreement with the finding of Stille et al (1). Similar results have been reported with chlorpromazine by Hudson and Domino (13). Haloperidol, however, has been reported to inhibit the facilitation and potentiate the inhibition of the PR due to stimulation of reticular forma tion (5).…”
Section: Methodssupporting
confidence: 89%
“…The antagonism of the decerebrate rigidity by the compound is in agreement with the finding of Stille et al (1). Similar results have been reported with chlorpromazine by Hudson and Domino (13). Haloperidol, however, has been reported to inhibit the facilitation and potentiate the inhibition of the PR due to stimulation of reticular forma tion (5).…”
Section: Methodssupporting
confidence: 89%
“…The cat's head was stereotaxically fixed and bipolar concentric stimulating electrodes were acutely implanted in the mesencephalic facilitatory (BF) and medullary inhibitory (BI) reticular formation. (For details see HUDSON and DOMINO, 1963). Stimulation of these sites for a period of 5 set at a frequency of 100 c/s with a pulse duration of 1 msec produced patellar reflex increment and decrement respectively.…”
mentioning
confidence: 99%
“…Henatsch & Ingvar (1956), however, used cats decerebrated by the anaemic method of Pollock & Davis (1930), in which rigidity is maintained by a-activity, and their results are probably therefore not comparable. Since in our preparations both tonic and reflex- induced a-discharges were abolished by chlorpromazine, it cannot be concluded that chlorpromazine has no effect on the a-motoneurone as proposed by Henatsch & Ingvar (1956) and Hudson & Domino (1963). Muscle relaxation produced by mephenesin could be due either to a direct depression of the a-motoneurone or to a reduction in its excitability by removal of interneuronal influences. The former seems unlikely since mephenesin does not abolish all voluntary movement, and the monosynaptic stretch reflex has generally been found to be unaltered.…”
Section: Discussionmentioning
confidence: 48%
“…Chlorpromazine also retained an effect on a-discharges after the preparation of a number of ventral roots for recording, which automatically cuts down the y-influence to the spindles, and after the splitting down of the motor nerve which greatly reduces the afferent input to the cord. The observations by other workers that chlorpromazine can reduce dorsal root or motor nerve evoked reflex discharges (Hudson & Domino, 1963) when presumably some of the afferent input must have been reduced by the requirements of the preparation also implies a direct effect of chlorpromazine on the a-system. Nevertheless, the main effect of chlorpromazine is presumably a depression of the y-motor system.…”
Section: Discussionmentioning
confidence: 87%